PENGARUH HARGA, PROMOSI, DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN IKAN MAS KOKI PADA KONSUMEN - Nurani; Gesti Ernestivita; Ika Nur Aini (Universitas Tulungagung, 2023)
Indonesia's natural conditions are in essence very supportive for cultivation, many goldfish are kept as freshwater ornamental fish which have attractive economic value, the increase in the marketing of ornamental fish commodities is none other than because many are fond of the business of raising aquarium ornamental fish to decorate the house through the types, size, color, body shape and ornamental fish are used to add to the beauty of the environment. Unfortunately, goldfish farming is still limited. The research was conducted in Sumberdadi Village in May 2023. Associative quantitative research design. The research population for goldfish consumers in Sumberdadi Village is 60 people. The independent variables are price, promotion and product quality, the dependent variable is the purchase decision. The research instrument is a questionnaire. Data were analyzed by multiple linear regression test.